The difficulties of students in learning mathematics by using development learning sequences approach in sd negeri no. 08 koto barapak kecamatan bayang - Pultion Trieni (Fakultas Sastra Universitas Ekasakti, 2018)
This study aims to improve learning achievement of Mathematics for children who have been difficulties in learning Mathematics using an approach Development Learning Sequences at fifth grade students in SD Negeri 08 Koto Berapak Kecamatan Bayang. The method used in this research is classroom action research method, while the strategy used as many as three cycles with the steps of preparing the plan, conduct the action, observation and reflection. Research subjects are students who have difficulty learning mathematics in class V, namely students whose math scores below the Minimum Exhaustiveness Criteria established school. Technique of collecting data is by interview, direct observation and document data. Analyze data is by interactive. From the overall cycle that has been done, it can be concluded that the approach of Development Learning Sequences can improve learning achievement of Mathematics for children who have been difficulties in learning at the fifth grade students in SD Negeri No.08 Koto Berapak Kecamatan Bayang.Each cycle has a positive impact on the handling of children with difficulties in learning Mathematics.Furthermore, the elementary school students have difficulty learning Mathematics, it is hoped this research can be used as a reference.